Jews and Genes : The Genetic Future in Contemporary Jewish Thought - Zoloth, Laurie; Dorff, Elliot N. (Book collections on Project MUSE., 2015)
Of the science of stem cell research / Elliot N. Dorff and Laurie Zoloth -- Applying Jewish law to stem cell research / Elliot N. Dorff -- Divine representations and the value of embryos : god's image, god's name, and the status of human nonpersons / Noam J. Zohar -- "Like water" : using Genesis to formulate an alternative Jewish position on the beginning of life / Yosef Leibowitz -- Reasonable magic : stem cell research and forbidden knowledge / Laurie Zoloth -- Summary of the science of genetic mapping and identity / Elliot N. Dorff and Laurie Zoloth -- Folk taxonomy, prejudice, and the human genome / Judith S. Neulander -- What is a Jew? The meaning of genetic disease for Jewish identity / Rebecca Alpert -- Yearning for the long-lost home : the lemba and the Jewish narrative of genetic return / Laurie Zoloth -- Summary of the science of genetic testing / Elliot N. Dorff and Laurie Zoloth -- Genetic testing in the Jewish community / Paul Root Wolpe -- Jewish genetic decision making and an ethic of care / Toby l. Schonfeld -- Summary of the science of genetic intervention / Elliot N. Dorff and Laurie Zoloth -- Some Jewish thoughts on genetic enhancement / Shimon Glick -- Curing disease and enhancing traits : a philosophical (and Jewish) perspective / Ronald M. Green -- Genetic enhancement and the image of god / Aaron l. Mackler -- "Blessed is the one who is good and who brings forth goodness" : a Jewish theological response to the ethical challenges of new genetic technologies / Louis E. Newman -- Jewish reflections on genetic enhancement / Jeffrey H. Burack -- Mending the code / Robert Gibbs -- Religious traditions in a postreligious world : does halakhah have insights for nonbelievers? / John Lantos -- How the unconscious shapes modern genomic science / Robert pollack -- To fix the world : Jewish convictions affecting social issues / Elliot N. Dorff